2023
DOI: 10.1002/adfm.202305249
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanorings and Nanobelts: Material Syntheses, Molecular Architectures, and Applications

Abstract: Carbon nanorings (CNRs) and carbon nanobelts (CNBs) of various sizes and innovative molecular architectures have ushered improvement in research in recent years. This serves as a prerequisite for further advances and applications, such as organic semiconductors and bottom‐up synthesis of single‐walled carbon nanotubes. Nevertheless, challenges such as high strain energy, excessive reactivity, end‐product stability, low‐scale yields, and side reactions inhibit material synthesis and applications. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 178 publications
1
6
0
Order By: Relevance
“…Moreover, owing to their double-stranded cylindrical skeleton, the radial π-conjugation in CNBs brings about more efficient orbital overlaps than those of the linear conjugation. As a result, CNBs are supposed to have remarkable charge transport properties and be generally more conductive than linear conjugated semiconductors, which was confirmed by both experimental and computational studies . Lastly, photophysical measurements , and excited-state simulations , demonstrated that CNBs exhibit peculiar photophysical and fluorescent properties, and as envisioned in ref , we could make use of the supramolecular chemistry of CNBs to modulate these properties by varying the guest species.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Moreover, owing to their double-stranded cylindrical skeleton, the radial π-conjugation in CNBs brings about more efficient orbital overlaps than those of the linear conjugation. As a result, CNBs are supposed to have remarkable charge transport properties and be generally more conductive than linear conjugated semiconductors, which was confirmed by both experimental and computational studies . Lastly, photophysical measurements , and excited-state simulations , demonstrated that CNBs exhibit peculiar photophysical and fluorescent properties, and as envisioned in ref , we could make use of the supramolecular chemistry of CNBs to modulate these properties by varying the guest species.…”
Section: Introductionsupporting
confidence: 59%
“…The translation vector, T⃗ = n a 1 + m a 2 , which is perpendicular to C⃗ , becomes the periodic (axial) direction of the resultant CNT. Accordingly, CNB structures have usually been designated the same chiral indices ( n , m ) as those for the CNTs where the CNBs are cut out from. , ,, Figure a demonstrates the construction of CNB (7,0) (represented by green rings) by rolling up the graphene nanosheet along the horizontal direction, C⃗ = O C = 7 a 1 .…”
Section: Enumeration and Nomenclature Of Cnb Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to aromatic hydrocarbon-based CNBs, heteroatom-embedded CNBs have also been reported. In 2019, Tanaka et al synthesized the first oxygen-embedded CNB by rhodium-catalyzed alkyne cyclotrimerization . Since then, CNBs with various topologies such as the armchair, zigzag, and Möbius-type CNBs, have been synthesized through the strategy developed by Tanaka’s group. Nitrogen-embedded CNBs have also been synthesized by our group, Wu et al, and Chen et al These heteroatom-containing nanobelts are also one of emerging molecules because of their unique properties derived from synergies between nanobelts and heteroatoms . Phenine nanotubes, which were first synthesized by Isobe et al in 2019, are also a kind of nanobelts when referring to the definition by Scott. , Long segments of CNTs are of great interest and should be one of the ultimate targets in synthetic chemistry.…”
Section: Synthesis Of Cnbs and Related Aromatic Beltsmentioning
confidence: 99%